Pockets : an intimate history of how we keep things close - Carlson, Hannah (Historian) (Algonquin Books of Chapel Hill, 2023)
"A social and design history of the sewn-in pocket, from the mid-1500s up to today, that uncovers what pockets reveal about us, our place in society, and how we move through the world"--